2018
DOI: 10.1002/app.47060
|View full text |Cite
|
Sign up to set email alerts
|

Pervaporation separation of an azeotropic mixture of a tetrahydrofuran–water system with nanostructured polyhedral oligomeric silsesquioxane embedded poly(vinyl alcohol)

Abstract: Cage -structured polyhedral oligomeric silsesquioxane (POSS) molecules were used as modifiers in the fabrication of poly (vinyl alcohol) (PVA) membrane for the separation of an azeotropic mixture of tetrahydrofuran (THF) and water system. Poly(ethylene glycol) and anionic octa(tetramethyl ammonium)-functionalized POSS were used for this study. The membranes exhibited excellent water selectivity and permeance because of their preferential interactions toward water molecules in the azeotropic THF-water mixture.I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…. The surface roughness value ( R q (nm) = 9.5) of pristine PVA was reported in our previous work . Compared to pristine PVA, PEG‐POSS embedded PVA‐PEO blend exhibits reduced surface roughness ( R q (nm) = 7.3).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…. The surface roughness value ( R q (nm) = 9.5) of pristine PVA was reported in our previous work . Compared to pristine PVA, PEG‐POSS embedded PVA‐PEO blend exhibits reduced surface roughness ( R q (nm) = 7.3).…”
Section: Resultssupporting
confidence: 58%
“…Both PEG‐POSS and Octa‐TMA‐POSS act as excellent mechanical reinforcing agents for the PVA‐PEO membrane and CMC enhances the miscibility of PVA‐PEO. In previous work, the mechanical properties of PEG‐POSS and Octa‐TMA‐POSS incorporated PVA were presented and it was observed that the mechanical stability of the PVA membrane increased in the presence of POSS molecules; this was further increased on blending with PEO . The blend membrane exhibits reduced elongation at break and improved stiffness due to good miscibility of the PVA and PEO polymers in the presence of CMC implying that the latter acts as a stabilizer of the PVA‐PEO blend.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…AFM images PEG-POSS-, Octa-TMA-POSS-, and m-POSS-incorporated PVA membranes are presented in our previous work. 34,35 The surface roughness parameter is found to be higher in PEG-POSS and m-POSS filled PVA membranes as compared to pure PVA whereas PVA/Octa-TMA-POSS system shows reduced surface roughness. The variation in the surface roughness by changing the functional group in POSS is probably due to the difference in the nature of interaction between the matrix and the filler at the PVA-POSS interfaces, resulting in the reorganization of chains of PVA on surfaces.…”
Section: Morphology Of Pva/poss Membranesmentioning
confidence: 97%
“…The cross-sectional morphology of PEG-POSS embedded PVA membrane (Figure 2(b)) shows a smooth and dense structure like pure PVA without forming any bulky agglomeration or any noticeable defects at the PVA-POSS interface. [34][35][36][37] This can be attributed to the dominating PEG side group (92 wt%) over the rigid siloxane core in PEG-POSS resulting in good interfacial bonding between polymer and POSS. However, in the case of Octa-TMA-POSS and m-POSS doped PVA membranes, spherical shape of the POSS particle were clearly visible.…”
Section: Morphology Of Pva/poss Membranesmentioning
confidence: 99%